2007
DOI: 10.1007/s12024-007-0016-3
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary investigation into the scavenging activity on pig carcasses in Western Australia

Abstract: Human remains exposed to an outdoor environment are subject not only to the process of decomposition, but also to the activity of scavenging fauna. The scavenging behavior of fauna can vary considerably with region and season, affecting the rate of decomposition, and more importantly, the accuracy of postmortem interval estimations. A thorough knowledge of the scavenging behavior of fauna present in the local environment is imperative for law enforcement and forensic investigators dealing with decomposed remai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
26
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 10 publications
6
26
0
Order By: Relevance
“…Badgers enter a state of torpor or semihibernation during winter and are most active from spring to fall, whereas foxes are active year round (4,31-33). Likewise, scavenging activity can be increased due to imminent breeding seasons and semihibernation which will require higher metabolic needs (34)(35)(36)(37)(38)(39)(40).…”
Section: Badgers Versus Foxesmentioning
confidence: 99%
“…Badgers enter a state of torpor or semihibernation during winter and are most active from spring to fall, whereas foxes are active year round (4,31-33). Likewise, scavenging activity can be increased due to imminent breeding seasons and semihibernation which will require higher metabolic needs (34)(35)(36)(37)(38)(39)(40).…”
Section: Badgers Versus Foxesmentioning
confidence: 99%
“…The majority of published literature on animal scavenging in a forensic context is case based [4][5][6][7] with only a few experimentally based studies reported [8,9]. In the ecological setting there have been many published papers on scavenging and surveys of scavenging guilds [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…There is a limited number of published papers on the scavenging activity of animals in Australia and even fewer addressing the taphonomic effects of scavenging [13,9].…”
Section: Introductionmentioning
confidence: 99%
“…More specifically within the U.K., common wild scavengers include wood mouse (Apodemus sylvaticus), grey squirrel (Sciurus carolinensis), carrion crow (Corvus corone), buzzard (Buteo buteo), Eurasian badger (Meles meles), and red fox (Vulpes vulpes) (Young et al, 2014a(Young et al, , 2014b. All of these scavengers are capable of causing significant soft tissue damage to surface deposited human remains (Mann et al, 1990;Haglund, 1992;Rothschild and Schneider, 1997;Byard et al, 2002;Asamura et al, 2004;Morton and Lord, 2006;Klippel and Synstelien, 2007;O'Brien et al, 2007). However, the bite force, jaw strength and body size of foxes and badgers enable them to not only scavenge human remains but also disarticulate and remove skeletal elements from deposit sites (Schmitz and Lavigne, 1987;Corbet and Harris, 1991;Alderton, 1994;Baryshnikov et al, 2003;Lee and Mill, 2004;Christiansen and Adolfssen, 2005;Sterry, 2005;Wroe et al, 2005;Christiansen and Wroe, 2007).…”
Section: Introductionmentioning
confidence: 99%